Urticarial hypocomplementemic vasculitis syndrome and systemic lupus erythematosus: a case report and review of the literature - Ouerdani, Yasmina; Ben Achour, Tayssir; Ben Hmid, Ahlem; Said, Fatma; Ayadi, Imen; Zehani Kassar, Alia; Jridi, Maysam; Ben Ghorbel, Imed; Naceur, Ines; Samoud, Samar; Galai, Yousr; Laadhar, Lilia; et al. (Frontiers in Immunology, 2025)
BackgroundHypocomplementemic urticarial vasculitis (HUV) syndrome is a rare form of small-vessel vasculitis characterized by a heterogeneous spectrum of clinical and biological findings. It is typically marked by chronic urticarial eruptions, hypocomplementemia and histopathological evidence of leukocytoclastic vasculitis. It may also involve multiple organ systems, with frequent articular, gastrointestinal, renal, and other systemic manifestations. The differential diagnosis with other systemic autoimmune diseases, particularly systemic lupus erythematosus (SLE), is often challenging due to their frequent association and the blurred boundaries between these entities.Case presentationWe report the case of a 34-year-old Tunisian man with an association of HUV and SLE. The diagnosis of SLE was established according to the 2019 European League Against Rheumatism (EULAR) criteria, based on the combination of inflammatory polyarthralgia, lymphopenia, a high titer of anti-nuclear antibodies, specific anti-Sm and anti-DNA antibodies, and consumption of C3 and C4 complement fractions. The diagnosis of HUV was made based on the presence of two major criteria: chronic urticaria and hypocomplementemia, along with four minor criteria: leukocytoclastic vasculitis, recurrent abdominal pain, episcleritis, and the presence of anti- C1q antibodies.ConclusionHUV and SLE share key clinical, immunological, and pathophysiological features, suggesting that they may lie along the same spectrum of autoimmune diseases. Their association, as seen in our patient, has been described in the literature. This overlap may result in more severe disease and requires close clinical follow-up.